Influence of Rock Block Content on Compaction Characteristics of Graded Coarse-Grained Fillers - Cai, Lili; Wang, Shengnian; Gao, Xinqun; Li, Guoyu (Frontiers in Physics, 2021)
The bearing capacity, stability, and durability of subgrade are affected by the compaction quality of fillers to a large extent. In this study, samples of graded coarse-grained fillers with different rock block contents were designed and prepared with the aid of an improved continuous gradation equation for coarse-grained soils. Then standard compaction tests of these samples with different water content conditions were conducted to understand the influence of rock block content on the compaction characteristics of graded coarse-grained fillers. Results show that the compaction curve peaks of graded coarse-grained fillers always increase with the rock block content. The maximum dry density of graded coarse-grained fillers increases linearly with the rock block content in approximation, while the optimal water content is the opposite. The optimal water content of graded coarse-grained fillers decreases in nonlinearity with characteristics of rapidly first and then slowly. Two empirical formulas about the rock block content were summarized for predicting the maximum dry density and optimal water content of graded coarse-grained fillers. The results of this study can provide a reference for the engineering application of graded coarse-grained fillers.